The Crime of Criminal Sentencing Based on Rehabilitation - Lopez, Louis R. (2010)
A lively debate began in the late 1970's on the topic of criminal sentencing. A major attack was launched on the indeterminate sentence and its companion concepts of probation and parole. Changes in state law on indeterminate sentencing were made but some writers rose to defend the indeterminate sentence and its justification - the rehabilitative theory of punishment. It is not clear how long and intense the struggle will be before the rehabilitative (a.k.a. reform, treatment) theory is put to rest or at least put in proper perspective; it should exist not as a basis for a sentencing plan but as an auxiliary and voluntarily administered method for helping prisoners to understand themselves and modify their conduct. The intention of this Article is to examine the inadequacy and lack of scientific development of the rehabilitative theory which precludes its use as a rationale behind criminal sentencing. Institutional problems in its practical application will be examined, but most importantly, questions will be presented about underlying flaws in the theory of how it is supposed to work even under ideal institutional conditions